LESSON PLAN - Pilu Reski (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2013)
A lesson plan is a teacher's detailed description of the course of instruction for one class. A daily lesson plan is developed by a teacher to guide class instruction. Details will vary depending on the preference of the teacher, subject being covered, and the need and/or curiosity of students. There may be requirements mandated by the school system regarding the plan.